Pengaruh Ekspansi Jaringan Distribusi, Strategi Promosi, dan Ketersediaan Stok Produk terhadap Keputusan Pembelian Konsumen Produk Fast Moving Consumer Goods (FMCG) Unilever di Indonesia - Fadli, La Ode; Ratnasari, Intan; Miswanto, Miswanto; Biyanto, Frasto; Siregar, Baldric (IAI Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of distribution network expansion, promotional strategies, and product stock availability on consumer purchasing decisions for Unilever's Fast Moving Consumer Goods (FMCG) products in Indonesia. With increasingly competitive market competition, this third factor is considered key to maintaining people's purchasing power. The research method used is quantitative descriptive-analytical with data collected through an online questionnaire based on a Likert scale of 1-5 distributed to 109 respondents. Data analysis was carried out using SPSS to test the validity, reliability, and influence of variables. The results of the study indicate that distribution network expansion (H1), promotional strategies (H2), and product stock availability (H3) individually have a positive and significant effect on consumer purchasing decisions. In addition, the third variable also has a simultaneous effect (H4). This conclusion provides practical implications for Unilever Indonesia to optimize distribution, promotion, and stock management strategies in influencing consumer decisions.